Geografia escolar: a mediação pedagógica na autoria de objetos de aprendizagem por alunos - Giordani, Ana Cláudia Carvalho (2010)
This research falls within the contexto of innovation in school geography-driven process of developing digital learning materials. The overall objective focused on proposing the development of learning objetcs (LOs) through by students in the school environment. The intrinsic goals were: a) reedem School Geography, the bias theoretical basis for the theoretical methodologies in accordance to the teaching and learning geographical contemporaries, b) contribute to digital inclusion, through action research with the development of LOs geographical via authorship of students, c) allow the subjects could become fluent in the Information and Communication Technologies (ICTs) used for generating power that are both readers and authorsin the media. The methodological approach of action research is organized into four cyclic spirals : thematic concern, categorization, organization and analysis. In each spiral held the movements of planning, action, observation and reflection, which make up the research that involved student-authors in the process of developing LOs. The research was conducted with fourth grade students from Public School Elementary Rio de Janeiro, located in the Cidade Baixa, the city of Porto Alegre/RS. Autonomy, interactivity and cooperation were the three dimensions of pedagogical mediation used as analytical categories. From the results, we highlight the following contributions : four LOs with by students, with the themes Music, Sports, Technology and Tourism on the Rio Grande do Sul. Besides the site developed as a repository for LOs, which makes such digital content to assist the processe of teaching and learning of teachers and students of geography in general. Conclusively, it is argued that, substained by the dimensions of pedagogical intervention, the authors of LOs by students enhances the learning of school geography in the fourth grade of elementary school.